Gender differentiation on the determinants and intensity of adoption of Purdue improved cowpea storage (PICS) bags in Northern Nigeria - Ndonkeu Nathanel Ndaghu; Tahirou Abdoulaye; Amina Mustapha; Djomo Choumbou Raoul Fani; Rayner Tabetando; Ukpe Udeme Henrietta; Sahbong Lucy Kamsang (Heliyon, 2023)
Postharvest and storage of agricultural produce such as cowpea remains a significant challenge in sub-Sahara Africa. This study assessed gender differentiation on the determinants and intensity of adoption of Purdue-improved cowpea storage (PICS) bags in northern Nigeria. Primary data was collected via a well-questionnaire from Kano, Kaduna, Gombe, Bauchi, Plateau, and the Niger States. Each State was purposively selected based on the concentration and availability of female PICS bag users. From the sampling frame 2989, 20% of male and female small-scale cowpea farmers were randomly selected, totalling 598 cowpea farmers. Descriptive and double-hurdle regression models were used. The result of the socioeconomic analysis indicated that farmers' mean age was 42 years, with an average of 8 persons per household and a dependency ratio of 1.19. Years of schooling were 10 with a farming experience of 25 years and 2.17 ha as the average farm size. Results of the Logit model in males were significant for (extension contact, PICS information from other farmers and radio sources, and cowpea income, bags non-available) and for females (age, awareness, extension contact, PICS information from other farmers and radio source, bags non-available). The truncated regression model was significant in males (cowpea income) and females (education, output, and bags non-available). Adopting PICS bag technology by cowpea farming households enhanced female farmers' adoption. Therefore, policymakers should implement methods to motivate female farmers to adopt this technology further.